Comment on "Indirect L to T point optical transition in bismuth nanowires" - Lovrinčić, Robert; Pucci, Annemarie (Physical review. B, Condensed matter and materials physics, 2010)
In the paper by A. J. Levin, M. R. Black, and M. S. Dresselhaus [Phys. Rev. B 79, 165117 (2009)] absorption features in infrared spectra are attributed to certain electronic transitions in bismuth nanowires. Our comment refers to the experimental spectra presented in this paper and explains how a better sample characterization would have improved the reliability of the conclusions from infrared spectra.